2009
DOI: 10.1161/circulationaha.108.843755
|View full text |Cite
|
Sign up to set email alerts
|

Location of Cardiac Arrest in a City Center

Abstract: Background— Public-access defibrillation with automated external defibrillators (AEDs) is being implemented in many countries worldwide with considerable financial implications. The potential benefit and economic consequences of focused or unfocused AED deployment are unknown. Methods and Results— All cardiac arrests in public in Copenhagen, Denmark, from 1994 through 2005 were geographically located, as were 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 187 publications
(89 citation statements)
references
References 41 publications
7
79
0
3
Order By: Relevance
“…These results were like the studies by Folke, et al [11] [12] and the study by Roger [13] that showed the application of defibrillation and chance of rescuing are higher in public spaces than residences when witnessed since the detection rate of ventricular fibrillation (VF) is higher.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results were like the studies by Folke, et al [11] [12] and the study by Roger [13] that showed the application of defibrillation and chance of rescuing are higher in public spaces than residences when witnessed since the detection rate of ventricular fibrillation (VF) is higher.…”
Section: Discussionsupporting
confidence: 84%
“…In advanced countries, the installation AEDs has been mostly recommended for public facilities [11] [12]. In Japan as well, emphasis had been placed on increasing the number of AED installations, but there has been a shift in thinking to the need to strategically deploy and manage AEDs now that the number of total installations exceeds 500,000 units.…”
Section: Discussionmentioning
confidence: 99%
“…As the costs for purchase and maintenance of PADs, and the training of personnel are relatively stable, cost‐effectiveness is dependent on the frequency of PAD use for OHCA (ie, the incidence of cardiac arrest in places with PAD deployment). Folke et al 29. calculated the cost‐effectiveness over various deployment strategies.…”
Section: Cost‐effectivenessmentioning
confidence: 99%
“…Only a small fraction of deployed PADs have been actually used 23, 24, 25. An extreme example was reported in Denmark where PAD deployment took place based on unguided initiatives, and none of the PADs were used during the study period 29. Mismatches in cities in North America, though differing in degree, have also been reported (Table 3).…”
Section: Issues Concerning Pad That Needs To Be Addressedmentioning
confidence: 99%
See 1 more Smart Citation